Review of "RADAR - Concise Course-Volumes 1 and 2" by Nadav Levanon - Baker, Chris J. (IEEE aerospace and electronic systems magazine, 2022)
Professor Nadav Levanon, one of the world's foremost authorities on radar, with a lifetime's experience and expertise of both teaching and researching, has published a new two-volume introductory e-book on radar, Radar—Concise Course, Volume 1 [1] and Radar—Concise Course, Volume 2 [2]. The radar community is fortunate to already have a number of wonderfully written texts introducing this complex and varied subject. Therefore, any new comer, covering this well-trodden territory, must successfully rise to the challenging trick of offering material that both enhances and enriches existing books, while simultaneously offering genuinely new perspectives that help to deepen the reader's overall understanding.